A Review of Energy Management of Renewable Multisources in Industrial Microgrids - Walter Naranjo Lourido; Fredy A. Sanz; Javier Eduardo Martinez Baquero (IAES Indonesian Section, 2023)
This review aims to consolidate recent advancements in power control within microgrids and multi-microgrids. It specifically focuses on analyzing the comparative benefits of various architectures concerning energy sharing and demand cost management. The paper provides a comprehensive technical analysis of different architectures found in existing literature, which are designed for energy management and demand cost optimization. In summary, this review paper provides a thorough examination of power control in microgrids and multi-microgrids and compares different architectural approaches for energy management and demand cost optimization.